Recent Advances in Laparoscopic Surgery - Sánchez Margallo, Francisco M.; Sánchez-Margallo, Juan A. (IntechOpen, 2019)
The implementation of laparoscopy has revolutionized surgery over the past few years, incorporating significant benefits for the patient. However, this evolution has also entailed many technical obstacles for surgeons. This book is for readers wanting to learn more about recent surgical techniques and technologies. Topics cover novel sophisticated approaches for single-site surgery, natural orifice transluminal endoscopic surgery, and transanal surgery, among others. Also included are reviews of new innovative surgical devices, robotic platforms, and methodological guidelines for improving surgical performance and surgeon ergonomics.